Circular - Middleton, J. S.
029-0014-001 NATIONAL COUNCIL OF LABOUR TRANSPORT HOUSE, SMITH SQUARE, LONDON. S.W.1 Trades Union Congress Secretary SIR WALTER M. CITRINE (Victoria 9820) The Labour Party Secretary J. S. MIDDLETON (Victoria 8016) Parliamentary Labour Party Secretary H. SCOTT LINDSAY (Whitehall 6240) Circ 119a July, 1937. Dear Comrade, Enclosed please find a new Appeal for the Spanish Children. We shall be glad to supply further quantities on application if you and your local comrades will undertake to distribute them in connection with a local Shilling Fund. Please be good enough to indicate your requirements on the following slip. With kind regards, Yours very sincerely, for the National Council of Labour, J. S. MIDDLETON Secretary. YOUR SHILLINGS WILL SAVE LIVES! Please send ............. copies of the above leaflet to: Name .......... Address ............. Organisation Date 292/946/29/14